Penguatan hukum masyarakat di era otonomi daerah - Kusdarini, Eny (Jurnal Civics: Media Kajian Kewarganegaraan, 2015)
Development cf law within human dan societallfie is influnced by manyfactors, wether inside of the society itself or fivm outside. In National politics oflaw of a country included Indonesia some changes happen and influence application the law. After Indonesian reform, regulation on local autonomy which is broad, tangible, and accountable needs reinforcement of law among society in its application. Itis urgently neccessary according to the principles of that the essence of democracy is form, by, and for the people. Reinforcement ofsocietallaw will be effective if there was effort to empower society by means of atmosphere or climate which enables the development ofpotentials ofit It will be if there is an attempt to protect weak society form being weaker.